Efecto toxicológico de extractos vegetales sobre Fusarium oxysporum bajo condiciones controladas. - Yugcha Quintana, Wilder Lenín (2015)
Toxicological effect of plant extracts of Nettle (Urtica dioica), dead flower (Tagetes erecta), basil (Ocimum basilicum) and rue (Ruta graveolens) on mycelial growth of Fusarium oxysporum was evaluated under controlled conditions. All plant extracts had a fungistatic effect on F. oxysporum. For the preparation of plant extracts Two methods of extraction (maceration infusion) was used, concentrations of extracts used were: 10, 25 and 50%, which were obtained from different studies extracts. The mycelial growth of F. oxysporum varied according to the type of extracts, concentration and extraction method, the control without extract in the culture medium increased PDA without any difficulty. Followed by the dead flower extract (T. erecta) that reached the highest average mycelial growth than other extracts studied, but less than witness who reached the highest mycelial growth The slower growth caused the extract nettle (U. dioica), with 50% concentration, in the method of extraction high statistical significance was found. The results obtained in this research supports the hypothesis that if there is a simple methodology for preparing traditional methods of plant extracts.